Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Numbered Heads Together (NHT) di Sekolah Dasar - Septrima, Yolanda; Lena, Mai Sri (Universitas Negeri Padang, 2021)
In elementary schools, at this time, the need for a learning model in integrated thematic learning that is suitable for students, especially during group discussions. This research starts from students who have not succeeded in exceeding the KKM, students are not seen actively learning, learning activities are also not visible because learning is still teacher-centered , and have not been seen working with his group of friends. And students do not understand the material that the teacher has. The Numbered Heads Together (NHT) cooperative model is an alternative way to solve this problem. The cooperative model is a method used in grouping students to complete tasks with one common goal. Describing the NHT-type cooperative model when integrated thematic learning in primary schools is the aim of this study. While the method in this research is library research. Library research is carried out by connecting the problems found then processing the data and analyzing the data obtained from books or journals. After getting the data needed to check the data. The results of the research that have been analyzed by 25 journals show that on average they are more likely to use the NHT-type cooperative model according to Trianto (2011). As well as integrated thematic learning in elementary schools can improve learning outcomes, motivation, activities, skills, cooperation, understanding of students.